Leading in Extraordinary Times: Documenting Pandemic Stories through Graphic Recording - Etmanski, Catherine (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2023)
This field report documents—through the use of graphic recordings—the “Leading in Extraordinary Times” webinar series that ran throughout the COVID-19 pandemic. Hosted by a team in the School of Leadership Studies at Royal Roads University in British Columbia, Canada, this series was notable for its use of a graphic recorder who joined each webinar and produced an image drawn in real time. We felt it was essential to document stories from this historical moment, not only through words and audio-visual recordings, but also through images. Following the webinar, each image was shared with participants, along with the video recording. At that time, free special topic webinars open to the public were still relatively novel. The success of this webinar series demonstrated that people were yearning for meaningful ways to connect online to reduce isolation and continue learning as wave after wave of the pandemic hit. We, therefore, saw a role we could play in both engaging and building community while hosting relevant, helpful, and timely dialogues throughout the pandemic. A summary of each webinar topic, together with the graphics and links to webinar recordings, are included in the report.